2023
DOI: 10.1039/d3sc03769j
|View full text |Cite
|
Sign up to set email alerts
|

Dimerization of confined Brønsted acids in enantioselective organocatalytic reactions

Ingolf Harden,
Frank Neese,
Giovanni Bistoni

Abstract: We shed light on the influence of the catalyst structure and reaction conditions on the spontaneity of the dimerization process for popular chiral organocatalysts derived from phosphoric acids using high-level quantum mechanical calculations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 86 publications
0
3
0
Order By: Relevance
“…For example, in the case of dimers, all the nondispersive terms in eq are sometimes summed to Δ E el‑prep , which leads to a simple decomposition of relative electronic energies into dispersive and nondispersive (e.g., steric/electrostatics) contributions. This simple strategy has found widespread applications in the study of LD effects in various fields of chemical research. …”
Section: Local Energy Decompositionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, in the case of dimers, all the nondispersive terms in eq are sometimes summed to Δ E el‑prep , which leads to a simple decomposition of relative electronic energies into dispersive and nondispersive (e.g., steric/electrostatics) contributions. This simple strategy has found widespread applications in the study of LD effects in various fields of chemical research. …”
Section: Local Energy Decompositionmentioning
confidence: 99%
“…In addition to the study of host–guest interactions, the LED scheme has also found widespread applications in catalysis. Importantly, this scheme can be used not only for unveiling LD contributions to the stability of reaction intermediates, ,, but also for identifying and quantifying the key covalent and noncovalent interactions responsible for the selectivity of chemical transformations. While a detailed exploration of our extensive work in this field is beyond the scope of this contribution, Figure b provides an illustrative example in the context of asymmetric catalysis …”
Section: Challenging Applicationsmentioning
confidence: 99%
See 1 more Smart Citation